Claw Abrasives in Layer Cages – A Review - Glatz, P.C. (International Journal of Poultry Science, 2001)
A review was undertaken to obtain information on the range of claw abrasives which could be used in layer cages to keep claws of hens blunt. In Europe a council directive has been issued which requires that all layer cages be fitted with suitable claw shortening devices. Research in Europe on claw abrasives suggest that abrasives reduce claw length of hens, improves feather cover, lowers mortality and reduces the incidence of scratches and entrapment injuries. More recent trials in Australia showed that claw abrasives could result in mortality in hens from prolapse and cannibalism. A low-cost, non-invasive method by which the claws of caged layers can be kept short and blunt can be achieved by fitting 8 mm strips of abrasive tape on the egg guard. Bird`s claws scrape against this tape while they are feeding. In Australia studies have shown that abrasive paint was more effective and more durable as a claw shortener than abrasive strips. The birds using the abrasive paint had the shortest claw length and lowest claw sharpness. Other work in Europe has shown that strips of sand fixed on the egg baffle with resin had a significant abrasive effect on the nails but by the end of the laying period large parts of the strip had been worn down. Claw shorteners have also been produced during cage manufacture by pressing a tread to make a perforated baffle. One of the most durable claw abrasives is a metal plate with abrasive iron filings. Other durable abrasives such as stone are also being tested for suitability as a claw abrasive.